15+2(3)=-3x

Simple and best practice solution for 15+2(3)=-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15+2(3)=-3x equation:


Simplifying
15 + 2(3) = -3x

Multiply 2 * 3
15 + 6 = -3x

Combine like terms: 15 + 6 = 21
21 = -3x

Solving
21 = -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
21 + 3x = -3x + 3x

Combine like terms: -3x + 3x = 0
21 + 3x = 0

Add '-21' to each side of the equation.
21 + -21 + 3x = 0 + -21

Combine like terms: 21 + -21 = 0
0 + 3x = 0 + -21
3x = 0 + -21

Combine like terms: 0 + -21 = -21
3x = -21

Divide each side by '3'.
x = -7

Simplifying
x = -7

See similar equations:

| -7(4x-5)+4=-28x+39 | | y=10,000(2)800/400 | | -75.00+7.50x=0 | | 78-100=-22 | | 4x^2-14x+2=0 | | (3x)(4x)=7 | | 4=-1 | | 5x^2-7x=18 | | 127=-9x-13-5x | | X-1=15/5 | | 4x+9=11x+5 | | 7g+10=-10+9g | | 3x+11=7x+5 | | 15+.25m=20m+.05 | | 3(4-5x)-6= | | 6+2y=y | | 15+.25m=.20m+.05 | | 15+.25m=.20+.05 | | 8z=2+9z | | 2k=-5+3k | | 6(2x+3)-9=4x+5+8x | | -8+10w=8w | | (X^8)^-3/4 | | -c=2c+9 | | 16-6=-8 | | 4h=10+9h | | Y=2x^2-4x+7 | | 45x^2-210x+245=0 | | -3=-19+n/5 | | 2x+x+10=-7x+10 | | 54x^2+72x+24=0 | | 24+8(z-3)=7z+5 |

Equations solver categories